Feasibility study of achieving reliable electricity supply using hybrid power system for rural primary schools in Iraq: a case study with umm qasr primary school - Hussam M. Almukhtar; Zaid H. Al-Tameemi; Karrar M. Al-Anbary; Mohammed K. Abbas; Dr. Hung-Yao Hsu; Dalya H. Al-Mamoori (Institute of Advanced Engineering and Science, 2019)
Electrical power is considered as a significant part of contemporary life, and an essential element for development. Fossil fuels have been utilized since the beginning of the twentieth century for electricity generation. However, fossil fuels depletion at the escalating pace as well as their formidable negative implications upon ecosystem contributed to increasing interest in harnessing renewable energy sources for producing electric power to meet the growing demand worldwide. In Iraq, the electrical supply is not sufficient to supply 12 hours a day of electricity. Many rural areas, particularly their schools are suffering from the electricity shortage such as Umm Qasr Primary School that located 20 km away from the city centre of Karbala city in the middle of Iraq. In order to overcome this issue, this paper proposes a hybrid system which relies on renewable resources and the local grid to electrify Umm Qasr Primary School. Various combinations of energy resources have been analysed by using HOMER software to estimate an optimum hybrid system. The analysis illustrates that the optimal configuration of the projected system is composed of 22.4 kW PV modules, 59 batteries, and 5738kWh purchased from the local grid which has reduced the net present cost(NPC)from US 163791 the current situation to US60,420 for the proposed system. The simulation findings also demonstrate that detrimental emissions have been reduced significantly.